Demographic Dynamics and the Empirics of Economic Growth - Sarel, Michael (Washington, D.C. : International Monetary Fund, 1994)
This paper examines the effects of demographic dynamics on the measured rates of economic growth. First, it develops a model of production with labor productivity that varies with age. Second, it uses macroeconomic and demographic data to estimate the relative productivity of different age groups. Third, it constructs a panel database of effective labor supply in order to reflect the changing age-structure of the population. Fourth, it decomposes the historical measured growth rates into effects of demographic dynamics and into 'real' growth rates, net of demographic effects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet